1978
DOI: 10.1063/1.324456
|View full text |Cite
|
Sign up to set email alerts
|

cw three-wave mixing in single-mode optical fibers

Abstract: Strong continuous three-wave mixing of 514.5-nm argon laser light in a single-mode fiber is reported. The effect, due to the third-order nonlinearity of silica, has been observed for light whose frequency spectrum consists of either a few discrete monochromatic frequency components separated by ∼1 GHz or a quasicontinuous distribution of frequencies having a spectral envelope ∼4 GHz wide. We show that the effect provides a simple and effective method for measuring the nonlinearity of silica. In the first manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(93 citation statements)
references
References 19 publications
1
88
0
4
Order By: Relevance
“…FWM has been studied in single-mode fibers, multimode fibers, and more recently, photonic crystal fibers (PCFs). [1][2][3][4][5][6][7][8] In most experiments, the red-shifted Stokes wave and the blue-shifted antiStokes wave are generated within the same mode as the pump light. In these cases, the phase-matching conditions require the pump to be in the vicinity of the zero dispersion wavelength (ZDW) of the propagating mode.…”
mentioning
confidence: 99%
“…FWM has been studied in single-mode fibers, multimode fibers, and more recently, photonic crystal fibers (PCFs). [1][2][3][4][5][6][7][8] In most experiments, the red-shifted Stokes wave and the blue-shifted antiStokes wave are generated within the same mode as the pump light. In these cases, the phase-matching conditions require the pump to be in the vicinity of the zero dispersion wavelength (ZDW) of the propagating mode.…”
mentioning
confidence: 99%
“…For example, phase matching of the FWM process in fibers can be achieved via different mode families of the fibers [93][94][95] and, similarly, in microresonators [96]. Generation of frequency harmonics by seeding modulated light to a fiber link [97], a sub-micron silicon-on-insulator rib waveguide [98], and a coupled-resonator optical waveguides [99] have also been observed.…”
Section: Resonant Wave Mixingmentioning
confidence: 92%
“…This was realized with respect to fiber optics four decades ago. For instance, phase-matched nonlinear mixing in an optical fiber was achieved using the dispersion of the waveguide modes to compensate for the dispersion of the material [93][94][95]. More recently it was found that micro-structuring of waveguides can provide control over the GVD to improve supercontinuum generation [236,237].…”
Section: Global Correctionmentioning
confidence: 99%
“…FWM is the process by which, electromagnetic fields of different frequencies, propagating simultaneously in a nonlinear medium interact through the third order nonlinear optical susceptibility of the medium, resulting in the generation of new frequencies. FWM in single mode fibers was first reported by Hill et al [1]. Since it can significantly influence the multi channel transmission systems, this phenomenon has been studied extensively in different types of fibers [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the use of dispersion shifted fiber (DSF) and choice of the signal wavelengths close to or at the zero dispersion wavelength are suggested as the best options to achieve phase matching and hence higher FWM efficiencies. A number of research papers have discussed this aspect [1,2,4]. However, at high signal powers, the non-linearity in the fiber also contributes to the phase mismatch through self-and cross-phase modulation.…”
Section: Introductionmentioning
confidence: 99%